Implementation of Accountant Ethics in Sundanese Cultural Perspective - Muhammad Aras Prabowo; Siti Nurul` Hikmah; Vita Febria Mutia Zein (Trescode Green Organization, 2025)
Ethics in accountants are better known to many people, especially for an accountant, which is the basis for the purpose of conducting this research. One of them is due to the lack of ethical awareness of an accountant. The accountant profession cannot be separated from the basic ethical principles of an accountant, an ethic should not be separated from everyday life either in carrying out activities or in work. The ethics of the accountant profession can be implemented in Sundanese culture. Sundanese culture that highly upholds the value of politeness or 'someah' in social matters. the concept of local education silih asah, silih asih, and silih asuh has a relationship with the ethics that are carried out in social life as well as in carrying out the profession as an accountant. The attitude of courtesy can be influenced by parental upbringing and environmental factors. The method applied in this research is literature. The literature method was chosen because it allows the author to gain an in-depth understanding of the title discussed. This research uses observation techniques, and document analysis to collect the necessary data. Documents in the form of journals were obtained from internet access which already contained related research journals.